Effect of Auxin and Cytokinin on Orchid Subculture Resulting from Coelogyne Crosses - Sri Hartati; Ahmad Yunus; Iistikharoh Iistikharoh (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2023)
The black orchid or Coelogyne is one of the native orchids of Kalimantan, widely cultivated in Indonesia. Several species of Coelogyne orchids have been crossed to obtain new superior-quality plants. Modifying the media, such as giving PGR, is necessary for good plant multiplication results. This research was conducted by changing MS growing media with ZPT BA and NAA. This experiment aimed to determine the effect of ZPT BA and NAA on the growth of orchid subcultures from a cross between Coelogyne pandhurata and Coelogyne rumphii. The study used a completely randomized design (RAL) with 2 factors, namely ZPT BA and NAA, each having a concentration of 0 ppm, 0.2 ppm; 0.4 ppm, and 0.6 ppm with 16 treatment combinations and 4 replications. They were implemented at the Laboratory Plant Physiology and Biotechnology, Faculty of Agriculture, UNS Surakarta, from November 2020 to March 2021. The variables observed included the number of shoots, plant length, plant weight, number of leaves, number of roots, root length, when roots appeared, and when shoots appeared. The results showed that BA 0.6 ppm gives the best output on the growth of the number of shoots, and NAA concentration of 0,2 ppm gives the best results on the variable number of roots. The combination of BA 0.6 ppm and NAA 0.2 ppm gave the best results on plant weight growth.